Pentingnya Sistem Pengendalian Manajemen dalam Pengelolaan Usaha Kecil dan Menengah di Kabupaten Banyumas, Jawa Tengah - Eko Suyono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This study aims to analyze the awareness of small and medium enterprises (SMEs) on the importance of applying management control system variables that include strategic planning, decision making, and evaluation and control in managing SMEs. By determining the criteria of certain company size in the process of sampling selection, this study ended up with 55 SMEs in Banyumas as a sample. This study employs both qualitative and quantitative approaches where the questionnaires distribution and interviews were conducted in October and November 2017. By using a descriptive analysis the findings shows that the owners of SMEs in Banyumas have high awareness on the importance of implementing strategic planning, decision making, and evaluation and control to manage their business. However, there are several weaknesses faced by SMEs to do so, for instance, low understanding of those issues due to low of the education level of the owners of SMEs and limited resources. It is important for Banyumas local government to address these issues so the SMEs will develop well in supporting the local economy.